Hirayama Disease: A 15-Year-Old Male With Progressive Distal Right Upper Extremity Weakness. Issue 2 (20th March 2023) - Gritsch, David; Mbonde, Amir A.; Khoury, Julie
Abstract : Introduction: Hirayama disease is a rare neuromuscular disorder characterized by abnormal forward displacement of the cervical spinal cord, resulting in focal ischemic changes of anterior horn cells. Case Report: A 15-year-old male presented with 6 months of progressive right upper extremity weakness. Electromyography/nerve conduction study indicated a chronic neurogenic process involving the C8-T1 myotome. Cervical spine magnetic resonance imaging in the neutral position demonstrated minor disk bulges without significant spinal canal narrowing. With flexion, there was a forward displacement of the dorsal dural sac and marked effacement of the subarachnoid spaces from vertebral levels C5 through C7. In addition, prominent flow voids were now seen in the dorsal epidural space consistent with engorged venous structures. Conclusion: The diagnosis of Hirayama disease requires a high index of suspicion, and imaging should include a series with the neck in a flexed position, as imaging in the neutral position is often unrevealing and the disorder can otherwise easily be missed.